235k views
20 votes
Can you guys help we with this question. ​​​​​​

Can you guys help we with this question. ​​​​​​-example-1
User Gui Ambros
by
4.4k points

2 Answers

5 votes
4r-2n=2

4r-10=2

4r=12

R=13
User James Bedford
by
4.6k points
6 votes

Answer:

40

Explanation:

(2x+1/(2x))^5 *(2x -1/(2x))^5

= ((2x)^2 -1/(2x)^2)^5 (a+b)*(a-b) =a2-b2

= (4x^2-1/4(x)^2)^5

now

x =4x^2. ,a = 1/4(x)^2 ,n =5

we have

general term = Cr *x^r *a^(n-r)

= Cr * (4x^2)^r * (1/4(x)^2)^(n-r)

= Cr *4^r * X^2r * 1/( 4^(n-r) *x^(2n-2r)

= Cr * 4^r/4^(n-r) * x^(2r)/x^(2n-2r)

= Cr * 4(2r-n) *x(4r-2n)

now for x^2

4r-2n = 2

4r -10=2

4r =12

r = 3

now for coeff

C(5,3) * 4^(2*3-5)

5!/(3!*(5-3)!) * 4

5*4/(2*1)*4

40

User AcademicRobot
by
4.7k points